2011
DOI: 10.1371/journal.pgen.1002187
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Endosymbiosis in a Cnidarian-Dinoflagellate Association: Differential Gene Expression and Specific Gene Duplications

Abstract: Trophic endosymbiosis between anthozoans and photosynthetic dinoflagellates forms the key foundation of reef ecosystems. Dysfunction and collapse of symbiosis lead to bleaching (symbiont expulsion), which is responsible for the severe worldwide decline of coral reefs. Molecular signals are central to the stability of this partnership and are therefore closely related to coral health. To decipher inter-partner signaling, we developed genomic resources (cDNA library and microarrays) from the symbiotic sea anemon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
170
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(193 citation statements)
references
References 78 publications
22
170
1
Order By: Relevance
“…Although previous work has investigated the downstream effectors of apoptosis such as caspases (43) and Bcl-2 family members (42), this is the first examination, to our knowledge, of the upstream ligands and receptors involved with initiating apoptosis in coral. Recently published transcriptomic studies of corals exposed to various environmental stressors have implicated members of the TNFSF/TNFRSF, as well as downstream proteins involved with apoptosis, supporting the ecological relevance of the TNF pathway in coral (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 79%
“…Although previous work has investigated the downstream effectors of apoptosis such as caspases (43) and Bcl-2 family members (42), this is the first examination, to our knowledge, of the upstream ligands and receptors involved with initiating apoptosis in coral. Recently published transcriptomic studies of corals exposed to various environmental stressors have implicated members of the TNFSF/TNFRSF, as well as downstream proteins involved with apoptosis, supporting the ecological relevance of the TNF pathway in coral (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 79%
“…Weis and Reynolds (400) subsequently used an anti-human CA immunoprobe and semiquantitative PCR to quantify increased amounts of the enzyme and its transcript, respectively, in the temperate sea anemone Anthopleura elegantissima when symbiotic versus aposymbiotic, and in the process they provided the first direct evidence of a host gene whose expression is influenced by its symbiotic dinoflagellates; these authors also, for the first time, reported a full-length CA cDNA sequence from a symbiotic cnidarian. Most recently, by employing a genomic approach, Ganot et al (122) have confirmed that CA expression is under the control of the symbiotic state.…”
Section: Inorganic Carbon Acquisition and Fixationmentioning
confidence: 99%
“…Two of the most highly upregulated genes in symbiotic anemones encode sym32, a protein described first in Anthopleura elegantissima (311,326,399) and more recently in Anemonia viridis (122), and calumenin (122). Ganot and coworkers (122) have developed a testable model for the role that these two proteins play in recognition and tolerance of symbionts.…”
Section: Figmentioning
confidence: 99%
“…Organic acids and pathway intermediates play essential roles in central metabolic pathways, including the TCA cycle, glycolysis, oxidative phosphorylation, the pentose phosphate pathway and gluconeogenesis (Livingstone, 1991;Ganot et al, 2011;Butterfield et al, 2013). They also have important functions in the production of co-enzymes and antioxidants, and as signalling molecules (Krüger et al, 2011).…”
Section: Organic Acids Intermediates and Antioxidantsmentioning
confidence: 99%